Analisa Dan Perancangan Sistem Informasi Monitoring Ketersediaan Kendaraan Operasional Dengan Metode Agile Berbasis Android - Agung Setia Budi; Mochammad Bagoes Satria Junianto (CV. Multi Kreasi Media, 2022)
An information system is a combination that is designed by people on a regular basis based on hardware, software, communication networks, and resources that can collect, enter and process, store, process, control and report data. Kalpika rides cooperative is a cooperative engaged in public transportation. The problems that occur at this time are the lack of information, the occurrence of struggles in the use of vehicles, there is no clear report and the input of daily transaction data is still written manually or written using a book. The solution to this problem is to build an information system for monitoring the availability of android-based operational vehicles using the Java programming language and designed using UML and using agile methods, where the stages of the method are system planning, implementation, testing, documentation, deployment, and maintenance.